2012
DOI: 10.1097/rct.0b013e31825586c0
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Reduction With Sinogram Affirmed Iterative Reconstruction Technique for Abdominal Computed Tomography

Abstract: Sinogram Affirmed Iterative Reconstruction-enabled reconstruction provides abdominal CT images without loss in diagnostic value at 50% reduced dose and in some patients also at 75% reduced dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
98
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 11 publications
9
98
1
1
Order By: Relevance
“…In the literature, there is a wide variation of dose-reduction results by using SAFIRE, [15][16][17][18][19][20][21] which makes it difficult to compare results. Differences might be partially explained by the inconsistency FIG 1. Boxplot diagrams.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, there is a wide variation of dose-reduction results by using SAFIRE, [15][16][17][18][19][20][21] which makes it difficult to compare results. Differences might be partially explained by the inconsistency FIG 1. Boxplot diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with expectations that image quality will be proportional to the dose level used when all other parameters are fixed. Our findings are concordant with previous studies using SAFIRE-based CT. Kalra et al 18 compared the use of abdominal CT reconstructed with SAFIRE with CT reconstructed with FBP and demonstrated a 50% reduced dose and, in some patients, a 75% reduced dose when using SAFIRE without a loss of diagnostic value. Similarly, Winklehner et al 19 showed the potential to reduce the radiation dose by Ͼ50% in body CTA studies by using SAFIRE without a deterioration in image quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effect of TOF is most pronounced in obese patients [5,25,26]. It has been shown that the SNR (as a property of the image) is proportional to the square root of the noise equivalent counts (NEC) [27], which is a property of the PET scanner. The increase in SNR is sometimes regarded as a gain in counts: a TOF image is equivalent to a non-TOF image obtained with a larger number of counts, where D/Δx is called the gain factor.…”
Section: Time-of-flightmentioning
confidence: 99%
“…With improvement in CT hardware and reconstruction algorithms, there are increasingly more dose-reduction strategies available for CT imaging. Examples are patient-specific adjustment of x-ray tube voltage in addition to modulation of x-ray tube current, and recent developments of iterative reconstruction algorithms [27]. When sufficient reduction in radiation dose at acceptable image quality for CT can be achieved, and in combination with dose reduction strategies for PET, as described in chapter 2, these strategies might become more suitable for use in routine clinical PET/CT imaging.…”
Section: Reduction Of Breathing Artefactsmentioning
confidence: 99%